EMPOWERMENT OF FISH PROCESSING AND MARKETING GROUPS IN THE CITY OF TOMOHON THROUGH ASSISTANCE WITH PRODUCT PACKAGING USING ENGLISH AND OTHER FOREIGN LANGUAGES : Pemberdayaan kelompok pengolah dan pemasaran ikan di kota Tomohon lewat pendampingan pengemasan produk menggunakan bahasa Inggris dan bahasa asing lainnya - Maya Pinkan Warouw; Jultje Rattu; Vivi Tumuju; Vany Kamu; Elvie Piri (SOSIOEDUKASI, 2023)
The community service activity aims to enhance the fish processing and marketing groups (Poklahsar) in the city of Tomohon, North Sulawesi. Tomohon is known for its cool and beautiful natural conditions and has traditional markets that serve as local shopping centers. This facilitates fish cultivators to sell their products locally, including through digital platforms like WhatsApp Business and Instagram. Despite local success, the marketing is still limited to the local scale, evident in packaging using local and Indonesian languages. To overcome this, the community service involves providing training, particularly in English, Japanese, and German, to the fish processing groups. English, being an international language, will be introduced for product descriptions on packaging and digital media. The goal is to enable Poklahsar in Tomohon to increase sales quantity and expand their market internationally.